Non-surgical Management of a C-shaped Mandibular Second Molar with Apical Periodontitis and External Root Resorption: A Case Report - Hamedi, Ali; Saeidi, Sorour; Kheradmand, Zakie (Iranian Endodontic Journal, 2025)
This case report describes the successful nonsurgical endodontic management of a mandibular second molar with a confirmed C-shaped canal configuration complicated by chronic apical periodontitis and active external inflammatory root resorption in a 16-year-old female patient. The patient presented with pain on biting, deep localized periodontal probing, and radiographic evidence of a large periapical radiolucency and resorptive changes in the distal root. Diagnostic tests confirmed pulpal necrosis and an endodontic–periodontal communication. Following access under magnification, the complex C-shaped canal system was negotiated and disinfected using 5.25% sodium hypochlorite, activated irrigation, and calcium hydroxide dressing. Because of apical resorption and an open apex, a 4–5 mm mineral trioxide aggregate apical plug was placed, followed by warm vertical obturation of the remaining canal system. The tooth was restored and monitored clinically/radiographically. At the 8-month follow-up, the patient was asymptomatic, probing depths had normalized, and radiographs demonstrated complete resolution of the periapical lesion with arrest of external root resorption. This case highlights that conservative endodontic therapy, supported by modern materials and careful disinfection, can achieve predictable healing even in teeth with complex morphology and resorptive defects. Early diagnosis and meticulous management are essential for a favorable outcome.